2013
DOI: 10.1155/2013/867938
|View full text |Cite
|
Sign up to set email alerts
|

Placental HSD2 Expression and Activity Is Unaffected by Maternal Protein Consumption or Gender in C57BL/6 Mice

Abstract: The placenta acts as a physiological barrier, preventing the transfer of maternal glucocorticoids to the developing fetus. This is accomplished via the oxidation, and subsequent inactivation, of endogenous glucocorticoids by the 11-β hydroxysteroid dehydrogenase type 2 enzyme (HSD2). Maternal protein restriction during pregnancy has been shown to result in a decrease in placental HSD2 expression and fetal glucocorticoid overexposure, especially late in gestation, resulting in low birth weight and “fetal progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…33,67 Furthermore, specific reduction in protein content of the maternal diet during early and mid, but not late, gestation in Wistar rats caused a reduction of placental HSD11B2 expression. 68 These findings have been supported by some, [69][70][71] though not all, 72 studies and collectively suggest that adequate protein intake is required to maintain optimal expression of placental HSD11B2. However, an excess of calories, predominantly derived from high fat and high sugar foods largely define Western dietary habits.…”
Section: Effects Of Dietary Composition On Placental Hsd11b2 Expressionmentioning
confidence: 76%
“…33,67 Furthermore, specific reduction in protein content of the maternal diet during early and mid, but not late, gestation in Wistar rats caused a reduction of placental HSD11B2 expression. 68 These findings have been supported by some, [69][70][71] though not all, 72 studies and collectively suggest that adequate protein intake is required to maintain optimal expression of placental HSD11B2. However, an excess of calories, predominantly derived from high fat and high sugar foods largely define Western dietary habits.…”
Section: Effects Of Dietary Composition On Placental Hsd11b2 Expressionmentioning
confidence: 76%
“…Other studies of the same strain of mice have found that a higher fat diet either reduces 11β-HSD2 mRNA expression [ 22 ] or has no effect [ 26 ]. A maternal low-protein diet did not affect placental 11β-HSD2 expression or activity in mice [ 41 ], in contrast to other species.…”
Section: Discussionmentioning
confidence: 99%